2022
DOI: 10.1039/d1tc05194f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical determination of the role of ions in atomic layer annealing

Abstract: The use of a heavier noble gas such as Kr in atomic layer annealing results in higher crystallinity due to higher momentum transfer leading to a more localized and intense surface heating effect occurring over picosecond timescales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Depositing high-quality AlN films at lower temperatures has been studied most intensively through plasma techniques such as plasma-enhanced atomic layer deposition (PEALD) and sputtering to deposit polycrystalline structures with 10–100 nm grain size. , Sputtering techniques significantly decrease the temperature required for metallic or ceramic thin film crystallization due to the promotion of surface diffusion driven by energetic ions . While these methods have yielded thermal conductivity values for AlN of 130 W/m·K at around 1 μm thickness, the deposition techniques have challenges. , Perez et al demonstrated record high thermal conductivity with micron thickness AlN sputter-deposition; however, this conventional DC sputter with balanced magnetron configuration suffered from slow deposition rates. ,,, The advanced high-power impulse magnetron sputtering (HiPIMS) has been utilized to create a reactive plasma with reduced hysteresis loops allowing for tighter control of operational point and enhanced the probability of reaction between nitrogen and gas phase aluminum in-between HiPIMS pulses, thereby enhancing the deposition rate. , Dense plasmas generated by HiPIMS also facilitate the growth of dense and smooth films . Bipolar HiPIMS, which combined HiPIMS and positive target bias, has been utilized in metal film deposition to further enhance surface diffusion during HiPIMS sputtering, which further densifies and smoothens films .…”
Section: Introductionmentioning
confidence: 99%
“…Depositing high-quality AlN films at lower temperatures has been studied most intensively through plasma techniques such as plasma-enhanced atomic layer deposition (PEALD) and sputtering to deposit polycrystalline structures with 10–100 nm grain size. , Sputtering techniques significantly decrease the temperature required for metallic or ceramic thin film crystallization due to the promotion of surface diffusion driven by energetic ions . While these methods have yielded thermal conductivity values for AlN of 130 W/m·K at around 1 μm thickness, the deposition techniques have challenges. , Perez et al demonstrated record high thermal conductivity with micron thickness AlN sputter-deposition; however, this conventional DC sputter with balanced magnetron configuration suffered from slow deposition rates. ,,, The advanced high-power impulse magnetron sputtering (HiPIMS) has been utilized to create a reactive plasma with reduced hysteresis loops allowing for tighter control of operational point and enhanced the probability of reaction between nitrogen and gas phase aluminum in-between HiPIMS pulses, thereby enhancing the deposition rate. , Dense plasmas generated by HiPIMS also facilitate the growth of dense and smooth films . Bipolar HiPIMS, which combined HiPIMS and positive target bias, has been utilized in metal film deposition to further enhance surface diffusion during HiPIMS sputtering, which further densifies and smoothens films .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a bombardment of energetic plasma ions onto the film surface is known to induce adatom displacement and surface diffusion, leading to densification and crystallization of the films, which is called atomic layer annealing (ALA). The ALA process further widens the range of film properties by precisely regulating the ion energy and fluence by controlling the plasma conditions (e.g., plasma power, pressure, exposure time, and bias). , Lee et al added an Ar plasma step at the end of the ALD cycle and confirmed that the effective depth of the plasma-assisted ALA was limited to the topmost five atomic layers in the PEALD AlN process . In addition, Go et al controlled the O 2 plasma exposure time during the deposition of PEALD TiO 2 to simultaneously synthesize discrete layers of crystalline TiO 2 and amorphous TiO 2 in a thin (<20 nm) film .…”
Section: Introductionmentioning
confidence: 99%